Imidazole synthesis by transition metal free, base-mediated deaminative coupling of benzylamines and nitriles. Issue 98 (23rd November 2017) - Das, Uttam Kumar; Shimon, Linda J. W.; Milstein, David
Abstract : An unprecedented transition metal free, base-mediated deaminative coupling of benzylamines and nitriles is reported. This protocol provides a practical strategy for the synthesis of 2, 4, 5-tri-substituted imidazoles with liberation of NH3 . Abstract : A transition metal free, straightforward synthetic method for the preparation of substituted imidazoles is reported herein. Base promoted, deaminative coupling of benzylamines with nitriles results in the one-step synthesis of 2, 4, 5-trisubstituted imidazoles with liberation of ammonia. This protocol provides a practical strategy for the synthesis of valuable imidazole derivatives from readily available starting materials.